Drivers and barriers to achieving quality in higher education - Eggins, Heather, 1939- (Sense Publishers, 2014)
"The topic of achieving and assuring quality in every higher education institution continues to be both relevant and urgent worldwide. This volume presents a considered discussion of a range of facets of the issue, drawing on the findings of a 3 year EU research programme involving seven countries: Czech Republic, United Kingdom, Latvia, Portugal, Poland, Slovakia and the Netherlands. Topics include access, student assessment, governance, stakeholders, academic faculty, information and the interface between the secondary and tertiary sectors. The authors, all of whom are drawn from the research teams, explore particular aspects of the research objectives. These aim to identify the drivers and overcome the barriers to establishing high quality in both European higher education, in relation to the Standards and Guidelines for Quality Assurance and, by implication, in worldwide higher education."